ОҚЫЎШЫ ЖАСЛАРДЫ КӘСИПКЕ ДУРЫС БАҒДАРЛАЎДЫҢ БҮГИНГИ КҮНДЕГИ ӘҲМИЙЕТИ - Утебаев, Т.Т.; Қдырбаева, Ҳ.М. (ILIM hám JÁMIYET, 2017)
The article deals with actual issues in directing the young people to the profession. The author analyses the factors in choosing the profession by the youth and becoming the specialists in future and gives advice to the youth in choosing the profession.